Before the Windrush : race relations in twentieth-century Liverpool - Belchem, John (Liverpool University Press, 2014)
'Before the Windrush' is a fascinating study that enriches our understanding of how the empire 'came home'. By drawing attention to Liverpool's mixed population in the first half of the 20th century and its approach to race relations, it provides historical context and perspective to debates about Britain's experience of empire in the 20th century.